General and specific combining ability of tropical and subtropical maize (Zea mays) lines. - Vergara-Ávila, Narciso (2005)
Twenty maizelines were crossed with six inbreds used as testers, with theobjective of examining their general and specific combiningability and determine their usefulness in a hybridizationprogram. The crosses were evaluated in three environmentsat Mexico during 1997. General combining ability (GCA)and specific combining ability (SCA) effects were calculatedusing a Line x Tester analysis. CML264 (1586 kg/ha) andCML319 (1285 kg/ha) were the highest GCA lines in thetropical and subtropical group, respectively. The highestSCA effects were for the crosses CML322 x M.L.S4-1 (1651kg/ha) and CML258 x SSE255-18-19 (1512 kg/ha). Theseresults indicate that it is possible to develop a hybrid programusing the best lines released by the International Maize andWheat Improvement Center (CIMMYT), and the best testersfrom UAAAN.